Post-soul satire : black identity after Civil Rights - Maus, Derek C.; Donahue, James J. (University Press of Mississippi, 2014)
"From 30 Americans to Angry White Boy, from Bamboozled to The Boondocks, from Chappelle's Show to The Colored Museum, this collection of twenty-one essays takes an interdisciplinary look at the flowering of satire and its influence in defining new roles in black identity. As a mode of expression for a generation of writers, comedians, cartoonists, musicians, filmmakers, and visual/conceptual artists, satire enables collective questioning of many of the fundamental presumptions about black identity in the wake of the civil rights movement. Whether taking place in popular and controversial television shows, in a provocative series of short internet films, in prize-winning novels and plays, in comic strips, or in conceptual hip hop albums, this satirical impulse has found a receptive audience both within and outside the black community. Such works have been variously called "post-black," "post-soul," and examples of a "New Black Aesthetic." Whatever the label, this collection bears witness to a noteworthy shift regarding the ways in which African American satirists feel constrained by conventional obligations when treating issues of racial identity, historical memory, and material representation of blackness. Among the artists examined in this collection are Paul Beatty, Dave Chappelle, Trey Ellis, Percival Everett, Donald Glover (a.k.a. Childish Gambino), Spike Lee, Aaron McGruder, Lynn Nottage, ZZ Packer, Suzan Lori-Parks, Mickalene Thomas, Touré, Kara Walker, and George C. Wolfe. The essays intentionally seek out interconnections among various forms of artistic expression. Contributors look at the ways in which contemporary African American satire engages in a broad ranging critique that exposes fraudulent, outdated, absurd, or otherwise damaging mindsets and behaviors both within and outside the African American community"--